Integrasi Sosialisasi Kesehatan dan Pelestarian Budaya Lokal Melalui Program KKN Universitas Abdurrab di Kelurahan Salo Timur - Erda Wati; Ardhezy Fajar Ramadhan; Rindiani Rindiani; Dea Utami Putri; Tesa Arta Maypia; Yulida Yulida; Salsa Febrianti; Dina Harahap; Shoky Fharenza Jordi; Rita Laila (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
The Community Service Program (KKN) is a platform for student dedication to the community that not only focuses on health aspects but also on strengthening cultural values and character education. The KKN activities of Abdurrab University in Salo Timur Village, Salo District, Kampar Regency were carried out by integrating health socialization and the preservation of local culture. The main programs include socialization on bullying at UPT SD Negeri 001 Salo, Clean and Healthy Living Behavior (PHBS), and the utilization of Family Medicinal Plants (TOGA) at MTS Darul Falah Salo, as well as reproductive health socialization and higher education information at SMA Negeri 1 Salo. This program is enhanced with maghrib recitation activities and Malay cultural training (kompang and rebana) aimed at instilling religious values while preserving cultural heritage. The results of the activities show an increased understanding among students and the community regarding health issues, as well as a high enthusiasm for activities that combine education, religiosity, and culture. This integration proves that community service (KKN) not only plays a role in the transfer of knowledge but also in building collective awareness, strengthening character, and preserving local identity.transfer of knowledge but also in building collective awareness, strengthening character, and preserving local identity.